KEBIJAKAN PAJAK DAN RETRIBUSI DAERAH TERHADAP PERANAN UMKM DALAM PEMBANGUNAN PEREKONOMIAN DAERAH - Nasution, M.Y.F. Hafidz; Rasjidi, Ira Thania; Paramyta, Dwi Sartika (Universitas Muhammadiyah Ponorogo, 2024)
Regional economic development must be treated as a collaborative process between the government and the people in creating stability and fairness on economic activities. MSMEs as a form of social economic entity holds a vital role both in economic development and regional development. Pursuant to Law No. 20/2008, MSMEs are granted by law various facilities to grow its businesses. On the other hand, Law No. 1/2022 that governs regional taxes and retributions is directly related with MSMEs’ position as the potential source of regional taxes and retributions needed for regional economic development. To date, the implementation of Law No. 1/2022 has not been optimal in supporting MSMEs’ growth as well as increasing MSMEs’ contribution on regional taxes and retributions. This is due to various of social factors which affects the implementation of Law No. 1/2022. Therefore, this research is aimed to analyzed from a socio legal perspective on the current regional taxes and retributions policy against MSMEs’ role in regional economic development. This research is made by using socio legal methodology and qualitatively analyzed. The research results indicates that despite the existence of Law No. 20/2008 and Law No. 1/2022 in providing a firm legal basis, the policy making in regional taxes and retributions budgeting capable of supporting MSMEs’ growth on one hand and increasing MSMEs’ contribution in regional taxes and retributions has yet to be met. Further, limited financial knowledge and awareness of MSMEs’ also caused minimum contribution in the regional economic development via regional taxes and retributions payment.